Three-dimensional modelling of shear keys in concrete gravity dams using an advanced grillage method - Mahdi Ben Ftima; Stéphane Lafrance; Pierre Léger (Water Science and Engineering, 2020)
Contraction joint shear keys are resilient features of gravity dams that can be considered to increase the sliding safety factors or minimise seismic residual sliding displacements, allowing costly remedial actions to be avoided. This paper presents a novel, robust, and computationally efficient three-dimensional (3D) modelling and simulation strategy of gravity dams, using a series of adjacent cantilever beam elements to represent individual monoliths. These monoliths are interconnected in the longitudinal direction by 3D no-tension link elements representing the lumped shear key stiffness contributions at a particular elevation. The objective is to assess the shear key internal force demands, including the axial force, shear, and moment demands. Shear key demand-capacity ratios can then be assessed with related multi-axial failure envelopes. The 3D link element stiffness coefficients were derived from a series of 3D finite element (FE) solid models with a detailed representation of geometrical features of multiple shear keys. The results from the proposed method based on advanced grillage analysis show strong agreement with reference solutions from 3D FE solid models, demonstrating high accuracy and performance of the proposed method. The application of the proposed advanced grillage method to a dam model with two monoliths clearly shows the advantage of the proposed method, in comparison to the classical approach used in practise.